Integrated biomolecular and bioprocess engineering strategies for enhancing the lipid yield from microalgae - Behera, Bunushree; Unpaprom, Yuwalee; Ramaraj, Rameshprabu; Gaanty Pragas, Maniam; Govindan, Natanamurugaraj; Balasubramanian, Paramasivan (Elsevier, 2021)
Algal biofuels have received wide attention in recent years for its potential to reduce the dependence on conventional fossil fuels. Despite the portrayed advantages of high growth rate, carbon sequestration and waste remediation; large scale application of microalgal biofuels is still lacking because of the lower percentage of extractable lipids obtained from the harvested biomass. Thus, there is a substantial impetus to analyse the strategies for enhancing the lipid profile and yield to improve the microalgal biofuel quality as well as to reduce the costs incurred at field scale. Several biochemical and molecular strategies to increase the algal lipid accumulation has gained huge scientific interest in recent years and have opened up new avenues for algal biorefinery. However, the time and cost involved as well as the ecological risks associated with real-time applications often restricts their utilization. The present review gathers a compendium of the key milestones associated with the recent approaches of biochemical, genetic and metabolic engineering for lipid quantity and quality enhancement. Biochemical and engineering aspects of coercing the cells to environmental stress and altering the mode of nutrition has been elucidated. The advancements in genetic and metabolic engineering, the associated risk factors and the future perspectives have been highlighted. Strategic integration of the bioprocess and biomolecular techniques to explore its synergistic impact to rationally engineer microalgae with improved triacylglycerols has been emphasized. Assessment of the long term risks associated herewith can be used to avert the challenges, making algal biofuels a commercial reality in future.